Siberian Crane - Status Report and Indian Situation - Dey, S. C. (Indian Forester, 1993)
The number of Siberian Crane (Grusleucogeranus) has declined in the current century. As against the figure of 200 birds which used to visit Bharatpur, only five were reported in the year 1993. Experiments were conducted to identify the specific flock which visits India from Siberia and whether the population increased by artificial supplementation through release of isolation seared Siberian Crane in captivity into the wild habitat. The exact migration route of common cranes from India to Siberia has been noticed. Specific action plan for individual countries has been given.